Assessment of Lung Eosinophils In Situ Using Immunohistological Staining - Nazaroff, Christopher D (Methods Mol Biol, 2021)
Eosinophils are rare white blood cells that are recruited from circulation to accumulate in the lung in mouse models of allergic respiratory inflammation. In hematoxylin–eosin (HE) stained lungs, eosinophils may be difficult to detect despite their bright eosin staining in the secondary granules. For this reason, antibody-mediated detection of eosinophils is preferable for specific and clearer identification of these cells. Moreover, eosinophils may degranulate, releasing their granule proteins into surrounding tissue, and remnants of cytolysed cells cannot be detected by HE staining. The methods here demonstrate the use of eosinophil-specific anti-mouse antibodies to detect eosinophil granule proteins in formalin-fixed cells both in situ in paraffin-embedded lungs, as well as in cytospin preparations from the lung. These antibody staining techniques enable either colorimetric or fluorescence imaging of eosinophils or their granule proteins with the potential for additional antibodies to be added for detection of multiple molecules.